Factors related to parental age of first concern in toddlers with autism spectrum disorder. (19th May 2017) - Matheis, Maya; Matson, Johnny L.; Burns, Claire O.; Jiang, Xinrui; Peters, W. Jason; Moore, Michael; de Back, Kaitlin A.; Estabillo, Jasper
ABSTRACT: Purpose : The age of first concern (AOC) of parents of children with autism spectrum disorders (ASD) has substantial implications for early diagnosis and intervention. The current study sought to determine the average AOC, what types of first concerns are most common, and what factors predict earlier AOC in toddlers with ASD. Methods : This study analyzed the predictive influence of the type of concern, symptom severity, medical diagnoses, and other independent variables on AOC among toddlers with ASD using multiple regressions. Results : The mean AOC was found to be 13.97 months (SD = 7.86). The most commonly reported first concern was speech/language. First concerns related to communication, speech/language predicted later AOC, while motor concerns predicted earlier AOC. Conclusions : Concerns that are more closely related to social communication deficits characteristic of ASD predicted later AOC. The implications of these findings on screening/assessment and intervention are discussed.